Quay Side, Trinidad - (:unkn) unknown (Unknown, 2011)
This postcard shows a ship departing from the Port of Spain harbour.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Ships--Trinidad and Tobago; Harbors--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Customhouses--Trinidad and Tobago; Architecture--Trinidad and Tobago; [1930]; Waterfronts--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Buildings--Trinidad and Tobago; Mountains--Trinidad and Tobago; Seas--Trinidad and Tobago; Jetties--Trinidad and Tobago; Piers--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago)